The synthesis and breast cancer inhibitory activity of cinnamic acid analogues based on the halogenated monoterpene pharmacophore - Chiwakata, Maynard Tendai (Rhodes University, Faculty of Pharmacy, Pharmacy, 2012)
Breast cancer is one of the leading causes of death, with mortality rate estimates of 465 000 deaths per annum. It is estimated that 1.3 million women are diagnosed with the disease each year especially in the developing countries. Current chemotherapy relies on the use of high doses of non-specific toxic agents that possess adverse side effects and compromise patient's compliance and adherence to treatment. Paclitaxel, one of the common drugs used in breast cancer chemotherapy results in sensory and motor neuropathy, whilst hormonal therapy e.g. Herceptin causes severe cardiovascular, gastrointestinal and cutaneous side effects. There has been a demand in developing newer cancer agents that demonstrate selective cytoxicity with minimal effect on normal body tissue. Numerous studies have shown that marine organisms produce a wide range of halogenated compounds that possess cytotoxic properties, and hence can be a source of new drug hits or leads for cancer therapy. Halomon, a polyhalogenated monoterpene from Portieria hornemannii, displayed interesting activity against brain, renal and lung cancer tumours with selective/differential cytotoxicity. This inspired us to focus our project on halogenated monoterpenes isolated from the same Rhodophyta class as P. hornemannii but with particular attention to Plocamium species. Several metabolites have been isolated from P. cornutum, P. corallorhiza and P. suhrii that possess interesting cytotoxicities against a breast cancer cell line (MCF7) and an oesophageal cancer line (WHCO1). The aim of the project was therefore centred at isolating target compounds for preliminary structure-activity studies against a breast cancer cell line, and use this information to synthesize a series of analogues that are more stable than the natural products and yet as active using a fragment-based type approach to map out pharmacophoric elements. Five metabolites were isolated from P. cornutum and five from P. corallorhiza. Cell-based assays were conducted using an MTT assay kit against MCF7 and MDA-MB-231 breast cancer cell lines and (1E,3E,5S,6R)-1,5,6-trichloro-2-(dichloromethyl)-6-methylocta-1,3,7-triene, isolated from P. cornutum was the most active with IC50 values of 3.0 Î¼M and 6.15 Î¼M respectively. Introduction of a terminal aromatic ring to enhance stability, together with varying substituents (H, CH3, CF3, Br, CN, CHO, CHCl2) on position 7 of the molecule, gave rise to a series of cinnamate ester derivatives inspired by (1E,3E,5S,6R)-1,5,6-trichloro-2-(dichloromethyl)-6-methylocta-1,3,7-triene. The analogues were synthesized from their benzaldehyde precursors via Aldol condensation, esterification and Wittig reactions. Their carboxylic acid counterparts were synthesized by hydrolysis of the parent esters in an attempt to promote water solubilities of the analogues. Biological activity assays were then conducted with the cinnamate analogues against the MDA-MB-231 breast cancer cell line using an MTT assay kit. Ester derivatives with -CHO and -CHCl2 functionalities had IC50 values of 43.45 Î¼M and 100.01 Î¼M respectively whilst the other ester derivatives were inactive. It was concluded that either an aldehyde (-CHO) or gem-dichlorides (-CHCl2) is specifically required for cytotoxic activity to be observed. None of the carboxylic acids were active which could have been due to failure of the compounds to enter the breast cancer cells and reach the target site because of their polar nature. Compounds with -CHO and -CHCl2 functionalities were therefore selected for future SARs studies.
Keywords: Halocarbons; Cancer -- Treatment; Breast -- Cancer -- Treatment